IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS DI SMAN 4 KABUPATEN GOWA - Zhiddiq, Sulaiman; Tahirah, Inas; Mannan, Abdul; Yusuf, Muhammad; Haris, Nurul Afdal (Universitas Negeri Makassar, 2025)
The application of conventional teaching methods that do not actively engage students has contributed to the low academic achievement in Geography among 11th-grade social science students at SMAN 4 Gowa Regency. This study aims to examine the effect of implementing the Jigsaw learning model on improving Geography learning outcomes among 11th-grade social science students at SMAN 1 Pangkep using a quasi-experimental method and a pretest-posttest control group design. The research sample consisted of two classes: an experimental class that applied the Jigsaw learning model and a control class that used conventional methods. The results showed a significant difference in students' learning outcomes between those taught using the Jigsaw learning model and those taught using conventional methods, with the experimental class achieving higher posttest scores and demonstrating increased student engagement in discussions and problem-solving. The study concludes that the Jigsaw learning model is effective in improving Geography learning outcomes, making it a viable alternative for educators in designing more interactive and student-centered learning strategies.